2000
DOI: 10.1034/j.1399-3003.2000.16a23.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in patients with obstructive sleep apnoea syndrome

Abstract: Cardiovascular disorders are common in patients with obstructive sleep apnoea syndrome (OSAS) but there is debate as to whether OSAS is an independent risk factor for their development, since OSAS may be associated with other disorders and risk factors that predispose to cardiovascular disease.In an effort to quantify the risk of OSAS patients for cardiovascular disease arising from these other factors, the authors assessed the future risk for cardiovascular disease among a group of 114 consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
85
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(94 citation statements)
references
References 32 publications
3
85
1
5
Order By: Relevance
“…But this did not provide an adequate control for the possible differences in medical history between patients with different severities of sleep apnoea. It is well-documented that by the time of diagnosis, sleep apnoea patients display a high rate of cardiovascular morbidity that significantly increases with apnoea severity [7,20]. Furthermore, several follow-up studies reported an increased incidence of cardiovascular morbidity in middle-age sleep apnoea patients who were free of such morbidity at the diagnosis [21][22][23], even without a change in apnoea severity [24].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…But this did not provide an adequate control for the possible differences in medical history between patients with different severities of sleep apnoea. It is well-documented that by the time of diagnosis, sleep apnoea patients display a high rate of cardiovascular morbidity that significantly increases with apnoea severity [7,20]. Furthermore, several follow-up studies reported an increased incidence of cardiovascular morbidity in middle-age sleep apnoea patients who were free of such morbidity at the diagnosis [21][22][23], even without a change in apnoea severity [24].…”
Section: Discussionmentioning
confidence: 95%
“…Patients with severe sleep apnoea have additional risk factors, which could be expected to greatly exacerbate their risk of mortality. By the time of their diagnosis a substantial proportion suffer from cardiovascular morbidity [19][20][21]. An independent association between cardiovascular morbidity and breathing disorders in sleep was reported even for patients with a very mild form of disordered breathing in sleep, that falls within the normal range of 1-10 respiratory events per hour of sleep [5,8,38].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described that OSAS is not an independent risk factor in the development of CV disorders [11][12][13]. However, other studies have stated that the rate of mortality is significantly higher in non-treated patients with AHI values over 20 [14], and the incidence of CVD in non-treated patients with moderate-severe OSAS is markedly increased compared to normal individuals or treated patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea (SA) is associated with increased risk of cardiovascular events, worsening of heart failure (HF), metabolic disturbances, and overall a reduced quality of life 1, 2, 3, 4. One study even found an increased risk of incident HF among men with obstructive sleep apnea (OSA) 5.…”
mentioning
confidence: 99%